2007
DOI: 10.2527/jas.2006-398
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of muscle hypertrophy on characteristics of Pectoralis major muscle and breast meat quality of broiler chickens1

Abstract: The structural and metabolic characteristics of the pectoralis major (P. major) muscle (i.e., breast muscle) and the quality of the resulting meat were studied in relation to breast muscle fiber development in broiler chickens. Six hundred birds originating from a commercial, grand parental, male heavy line (Hubbard-Europe, Châteaubourg, France) were kept under conventional breeding methods until their usual marketing age of 6 wk. For all birds, the plasma creatine kinase activity and the P. major muscle fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
117
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(157 citation statements)
references
References 32 publications
21
117
3
5
Order By: Relevance
“…Collin et al (2007) show that the MPS of 43-dayold broiler had a lower pH 24 h and higher drip loss if temperature was increased to 39.58C between ED 8 and 10. With regard to the meat colour values the gender difference of the L* values 20 min p.m. agree with an investigation by Berri et al (2007), although this result should not be overstated as the difference was only of visible 20 min p.m. The increase in the lightness, redness and yellowness values between 20 min and 24 h p.m. in the presented study is in accordance with the investigation of Petracci and Fletcher (2002).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Collin et al (2007) show that the MPS of 43-dayold broiler had a lower pH 24 h and higher drip loss if temperature was increased to 39.58C between ED 8 and 10. With regard to the meat colour values the gender difference of the L* values 20 min p.m. agree with an investigation by Berri et al (2007), although this result should not be overstated as the difference was only of visible 20 min p.m. The increase in the lightness, redness and yellowness values between 20 min and 24 h p.m. in the presented study is in accordance with the investigation of Petracci and Fletcher (2002).…”
Section: Discussionsupporting
confidence: 91%
“…Yahav et al (2004a) treated broiler eggs between ED 8 and 10 at 39.58C for 3 h/ day and analysed 4 day chicks, Maltby et al (2004) treated turkeys eggs between ED 9 and 12 at 38.58C and killed the animals at day 16 post-hatch, whereas Hammond et al (2007) treated laying hen eggs at 38.58C between ED 4 and 7 and killed the foetuses at ED 18. The histological analysis of the female MPS partly agrees with a study by Berri et al (2007) who showed that broiler hens have larger muscle fibre areas. The significantly lower fibre areas in the HT hens indicate that the manipulation during embryogenesis decreased the MFN.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The change is influenced by the decreasing pH values. Owens et al (2000), Petracci et al (2004) and Berri et al (2007) showed a negative correlation between the pH and the lightness of the meat. The pH values also explain the lightness differences between the MPS and MG, as the MG had generally higher pH values.…”
Section: Discussionmentioning
confidence: 91%